Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Terhadap Hasil Belajar IPA Terpadu Siswa Kelas VIII SMP Negeri 22 Merangin Tahun Pelajaran 2018/2019 - Tutut Puji Astuti; Eko Wulandari; Rivo Yulse Viza (Pendidikan Biologi STKIP YPM Bangko, 2018)
This research is motivated by result of integrated science learning student of class VII still have not reached the KKM that is 75. One of the learning models that can improve student learning outcomes is to use the TPS type cooperative learning model. This study aims to find out and describe the Think Pair Share (TPS) type of cooperative learning better than conventional models on integrated science learning outcomes for grade VIIIstudent of SMP Negeri 22 Merangin in 2018/2019 academic year. This type of research is experimental research, the research design is post test only control design. The population in this study were all eight grade student of SMP 22 Merangin in the 2018/2019 school year consisting of 2 classes. The sampling technique in this study is total sampling, and to determine the experimental class and control class using simple random sampling. Data collection technigues are test techniques, trought essay tests totaling 8 items. Data analysis techniques used to test hypotheses are t-test. The result of the study, in the experimental class obtained an average value of 78,6, while in the control class obtained an average value of 75,05, then the data was analyzed using the t-test. Hypothesis test results are obtained, t-count=1,803 an t-table=1,689. Because t-count > t-table then Ho is rejected and Ha is accepted. So it can be concluded that the integrated science learning outcomes using cooperative learning model type Think Pair Share (TPS) is better than using conventional learning model class VIII SMP Negeri 22 Merangin in the 2018/2019 school year.